Effects of information on consumer attitudes towards gene-edited foods: a comparison between livestock and vegetables - Naoko Kato-Nitta; Yusuke Inagaki; Tadahiko Maeda; Masashi Tachikawa (CABI Agriculture and Bioscience)
Abstract Background This study statistically explores the relationship between information provision and peoples’ attitudes towards the application of gene-editing technology to food, by contrasting cases of gene-edited livestock and vegetables in Japan. Japanese food producers and researchers are optimistic about the application of the clustered regularly interspaced short palindromic repeats (CRISPR) approach to food. Due to the strict regulations regarding genetically modified (GM) food, GM crops are not commercially cultivated in Japan. Consumers worldwide have concerns about application of this technology to food. Further examination of this issue for Japanese consumers with lower acceptance towards GM food should provide essential information for global agricultural communities. Methods Using a web survey, split-ballot experimental design was used to randomly assign the respondents into two groups: (1) the animal group, for which information on breeding technologies, including gene editing, was provided using pig illustrations. (2) The plant group, for which information was provided using tomato illustrations. Multivariate analysis of variance and post-hoc t-tests were applied to examine the statistical differences between the plant and animal groups for attitudes towards gene-edited livestock and vegetables. Statistical analyses were conducted to examine if scientific knowledge influences these attitudes. Results Respondents found gene-edited vegetables more beneficial than gene-edited livestock. Their agreement was stronger for vegetables than for livestock. Respondents’ attitudes towards gene-edited livestock differed depending on whether they were shown pig illustrations or tomato illustrations. The plant group scored significantly lower regarding gene-edited livestock compared to the animal group. No statistical difference was observed between the two groups in the case of gene-edited vegetables. Furthermore, the higher science literacy group always scored higher regarding improvements in vegetable breeding, but this was not concordant regarding improvements in livestock breeding. Conclusions People were more concerned about gene-edited livestock than gene-edited vegetables. The respondents who were provided information with tomato illustrations in advance demonstrated lower acceptance towards gene-edited livestock than those who were provided information with pig illustrations. Applying the technology to livestock, such as size enlargement for improvements, might be considered as risky by the public, in contrast with vegetables.